Using Concept as Method in Educational and Social Science Inquiry. (November 2017) - Taguchi, Hillevi Lenz; St.Pierre, Elizabeth Adams
This article introduces this special issue of Qualitative Inquiry focused on using concepts as methods in educational and social science inquiry to account for an ontological arrangement in which humans are not seen as the only beginning of inquiry and in which transcendental and/or radical empiricism is in play. With the articles of this issue, we would like to offer a partly new or reconceptualized way of doing educational inquiry: a way where concepts—acts of thought—are practices that reorient thinking, undo the theory/practice binary, and open inquiry to new possibilities.